Purification and Characterization of Two Extracellular Xylanases from Penicillium sclerotiorum: A Novel Acidophilic Xylanase - Knob, Adriana [UNESP]; Carmona, Eleonora Cano [UNESP] (Humana Press Inc, 2010)
Two xylanases from the crude culture filtrate of Penicillium sclerotiorum were purified to homogeneity by a rapid and efficient procedure, using ion-exchange and molecular exclusion chromatography. Molecular masses estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis were 23.9 and 33.1 kDa for xylanase I and II, respectively. The native enzymes' molecular masses of 23.8 and 30.8 kDa were estimated for xylanase I and II, respectively, by molecular exclusion chromatography. Both enzymes are glycoproteins with optimum temperature and pH of 50 A degrees C and pH 2.5 for xylanase I and 55 A degrees C and pH 4.5 for xylanase II. The reducing agents beta-mercaptoethanol and dithio-treitol enhanced xylanase activities, while the ions Hg(2+) and Cu(2+) as well the detergent SDS were strong inhibitors of both enzymes, but xylanase II was stimulated when incubated with Mn(2+). The K (m) value of xylanase I for birchwood xylan and for oat spelt xylan were 6.5 and 2.6 mg mL(-1), respectively, whereas the K (m) values of xylanase II for these substrates were 26.61 and 23.45 mg mL(-1). The hydrolysis of oat spelt xylan by xylanase I released xylobiose and larger xylooligosaccharides while xylooligosaccharides with a decreasing polymerization degree up to xylotriose were observed by the action of xylanase II. The present study is among the first works to examine and describe an extracellular, highly acidophilic xylanase, with an unusual optimum pH at 2.5. Previously, only one work described a xylanase with optimum pH 2.0. This novel xylanase showed interesting characteristics for biotechnological process such as feed and food industries.
Keywords: Penicillium sclerotiorum; Xylanase; Enzyme purification; Enzyme characterization